1997
DOI: 10.5636/jgg.49.1079
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Signature of Magnetic Cavity Mode Oscillations in ISEE Spacecraft Observations.

Abstract: The structure of magnetohydrodynamic waves in the terrestrial magnetosphere is controlled by the dispersion relations of the wave modes, the inhomogeneities of the system and the boundary conditions. If the waves are confined within the magnetospheric cavity with proper boundary conditions, two types of spectra are predicted by MHD theory. One is a discrete compressional spectrum and the other is a continuous shear Alfven spectrum. The discrete spectrum refers to compressional eigenmodes with spatially constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 37 publications
5
35
0
Order By: Relevance
“…In addition, its dimensions are continually changing in response to the solar wind so the cavity properties are always changing. These facts have made it difficult to demonstrate conclusively the existence of cavity modes experimentally (Radoski, 1971;Crowley et al, 1987;Samson et al, 1991;Kivelson et al, 1997). There is, however, some indirect evidence discussed next that they exist and are an important factor in determining the properties of ground ULF waves.…”
Section: Cavity Resonancesmentioning
confidence: 90%
“…In addition, its dimensions are continually changing in response to the solar wind so the cavity properties are always changing. These facts have made it difficult to demonstrate conclusively the existence of cavity modes experimentally (Radoski, 1971;Crowley et al, 1987;Samson et al, 1991;Kivelson et al, 1997). There is, however, some indirect evidence discussed next that they exist and are an important factor in determining the properties of ground ULF waves.…”
Section: Cavity Resonancesmentioning
confidence: 90%
“…The results of such a test are reported in the present paper. One possible signature of a fast mode resonance was presented by Kivelson et al [1997] who observed a constant tone at 24 mHz during a spacecraft radial pass through the plasma trough. This event is discussed later in the present paper.…”
Section: Introductionmentioning
confidence: 97%
“…However, because the standing resonance decays rapidly, this may not rule out some global mode contribution. As noted above, in the case examined by Kivelson et al [1997], the putative cavity mode amplitude died away quickly unless the IMF cone angle remained "quasi-parallel" (i.e., < 45°) and thus satisfied the condition for transmission of wave power in the Pc3-4 band from the solar wind to the magnetosphere. Intermittent bursts of input power, which need not be coherent, could then account for the temporal variability reported by Chi and Russell.…”
Section: Cavity/waveguide Modesmentioning
confidence: 99%
“…Waters et al [2002] identified characteristics of the fast mode resonances in simulations (frequency independent of L over a range of L in the plasmasphere or plasma trough, 90° phase difference between azimuthal electric and fieldaligned magnetic perturbations, expected nodal structure of the compressional magnetic field) and looked for these characteristics in several cases of putative fast mode resonances in the magnetosphere. In the event described by Kivelson et al [1997], they find no significant maxima in cross phase of the parallel field component evaluated from ISEE 1 and 2 magnetometer data for separations of 400 to 620 km. They acknowledge that it is unlikely that the signature would be detectable for such small separations for the low values of Q that apply in the magnetosphere.…”
Section: Cavity/waveguide Modesmentioning
confidence: 99%
See 1 more Smart Citation